One piece. Collection no. 07 [videorecording (DVD)]. - Clinkenbeard, Colleen; Christian, Luci; Oda, Eiichirō, 1975- (Funimation, 2012)
Nami, Chopper, Zoro, and Robin are trapped on the Going Merry, and it is taken over by a monster lobster. Luffy must go to the sacred grounds of Upper Yard to rescue his crew.